Low frequency of toothbrushing practices is an independent risk factor for diabetes mellitus in male and dyslipidemia in female: A large-scale, 5-year cohort study in Japan. Issue 2 (August 2017) - Kuwabara, Masanari; Motoki, Yoko; Sato, Hiroki; Fujii, Mizue; Ichiura, Kayoko; Kuwabara, Kazumichi; Nakamura, Yosikazu
Abstract: Background: We previously reported the association between toothbrushing practices and diabetes mellitus (DM) and dyslipidemia (DL) in a cross-sectional study. This study was conducted to clarify whether low frequency of toothbrushing practices is an independent risk factor for DM and DL using a follow-up design. Methods: This study was a 5-year retrospective cohort study at St. Luke's International Hospital, Tokyo, Japan. We analyzed study subjects between 30 and 85 years old in 2004, who underwent annual medical examination both in 2004 and 2009. We compared the cumulative incidences of developing DM, DL, hypertension (HT), and hyperuricemia (HUA) between 2004 and 2009 among 3 groups: toothbrushing practices 'after every meal, ' 'at least once a day, ' and 'less than once a day'. Furthermore, we analyzed odds ratios (ORs) of risk for developing DM and DL by sex after making adjustments for age, obesity, DM, DL, HT, and HUA between two groups: 'after every meal' and 'not after every meal.' Results: The number of study subjects was 13, 070. Of 13, 070 study subjects, 575 had DM, 5118 had DL, 2599 had HT, and 1908 had HUA in 2004. We excluded the subjects with each disease in 2004. The cumulative incidences (rates) of DM, DL, HT, and HUA between 2004 and 2009 were 318 (2.5%), 1454 (18.3%), 1108 (10.6%), and 489 (4.4%), respectively. Toothbrushing practices 'not after every meal' was a significant risk factor for developing DM in male [OR: 1.43; 95% confidence interval (CI), 1.040–1.970] and developing DL in female (OR: 1.18; 95% CI, 1.004–1.383) compared with toothbrushing practices 'after every meal.' Conclusion: Toothbrushing practices 'after every meal' prevented developing DM in males and DL in females significantly. Toothbrushing practices may be beneficial to reduce developing risk factors for cardiovascular disease.